Effectiveness and Safety of Anlotinib Combined with PD-1 Blockades in Patients with Previously Immunotherapy Treated Advanced Non-Small Cell Lung Cancer: A Retrospective Exploratory Study - Dou XJ; Ma RY; Ren DW; Liu Q; Yan P (Lung Cancer: Targets and Therapy, 2024)
Xue-Jun Dou,1,* Run-Yang Ma,1,* De-Wang Ren,1 Qiang Liu,2 Peng Yan3 1Department of Thoracic Surgery, Aerospace Center Hospital, Beijing, 100049, People’s Republic of China; 2Department of Thoracic Surgery, Peking University International Hospital, Beijing, 102206, People’s Republic of China; 3Department of Respiratory Medicine, China Aerospace Science & Industry Corporation 731 Hospital, Beijing, 100071, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiang Liu, Department of Thoracic Surgery, Peking University International Hospital, Beijing, 102206, People’s Republic of China, Tel +86 15901472799, Email liuqiang8548@163.com Peng Yan, Department of Respiratory Medicine, China Aerospace Science & Industry Corporation 731 hospital, Beijing, 100071, People’s Republic of China, Email yanpeng301@163.comObjective: This study aimed to investigate the effectiveness and tolerability of anlotinib plus PD-1 blockades in patients with previously immunotherapy treated advanced non-small-cell lung cancer (NSCLC).Methods: A total of 67 patients with previously immunotherapy treated advanced NSCLC who received anlotinib plus PD-1 blockades in clinical practice were screened retrospectively. All the PD-1 blockades used in this study were approved in China and consisted of sintilimab, camrelizumab, tislelizumab and pembrolizumab. Effectiveness and safety of anlotinib plus PD-1 blockades were assessed, and all patients were followed up regularly. Clinical significance between response status to previous immune-related treatment regimens and therapeutic outcomes of anlotinib plus PD-1 blockades was further explored.Results: The best overall response among the 67 patients suggested that a partial response was observed in 16 patients, stable disease was noted in 41 patients and progressive disease was found in 10 patients, which yielded an objective response rate of 23.9% (95% CI: 14.3– 35.9%) and a disease control rate of 85.1% (95% CI: 74.3– 92.6%). Prognostic outcomes indicated that the median progression-free survival (PFS) was 6.1 months (95% CI: 2.37– 9.83) and the median overall survival (OS) was 16.5 months (95% CI: 10.73– 22.27). Exploratory analysis highlighted that patients who were intolerant to previous immune-related regimens (17 patients) might have a superior prognosis (median OS: 22.3 months vs 12.5 months, P=0.024). Additionally, adverse reactions with any grades during anlotinib plus PD-1 blockades administration were observed in 62 patients (92.5%), of which 31 patients (46.3%) had ≥grade 3 adverse reactions. Most common adverse reactions were fatigue, hypertension, diarrhea and hepatotoxicity.Conclusion: Anlotinib plus PD-1 blockades demonstrated promising effectiveness and tolerable safety in patients with previously immunotherapy treated advanced NSCLC. Those who were intolerant to previous immune-related regimens might benefit significantly from treatment with anlotinib plus PD-1 blockades. This conclusion should be confirmed in future studies.Keywords: previously immunotherapy treated NSCLC, anlotinib, PD-1 blockades, effectiveness, safety